Visualization of Java workloads using ternary diagrams. - Dujmović, Jozo (Software engineering notes.)
In this paper we investigate the use of ternary diagrams for visualization of Java workloads, and show how to use this technique for an analysis of JVM98 SPEC benchmarks. Ternary diagrams present workloads as points in plane with respect to three characterization parameters. They can be combined with other visualization techniques based on dendrograms, histograms, pie charts, and Kiviat graphs. Java workloads are characterized using dynamic frequencies of bytecodes (or timed bytecodes). Related bytecodes are grouped, and their frequencies aggregated, to reduce dimensionality. We propose four ways for grouping Java bytecodes and use them to analyze properties of Java workloads. Our methodology is generally applicable in all cases where workload characterization is based on compiler-generated intermediate or machine code.